TEST AND ANALYSIS ON THE MECHANICAL PROPERTIES OF CASSAVA STALKS - Z. Xue; J. Zhang; Y. L. Zhang; C. B. Li; S. Chen (Journal of Animal and Plant Sciences, 2015)
The mechanical properties of the cassava stalk play an important role in the design of cassava harvesting and cassava stalk recycling machines. Axial and radial compression tests with different loading rates were conducted on 3 groups of cassava stalks with 5 moisture contents in 3 stalk levels at the harvest time. Sliding cutting tests as well as cutting tests with different loading rates and cutting angles were conducted on 5 groups of root samples of cassava stalks having 5 moisture contents at harvest time. The overall failure loads and the strengths of the cassava stalks were analyzed with respect to the different factors under investigation in this study using SAS software. The following results were obtained: in the axial compression of the stalks, the average values of the failure load and compressive strength were respectively for different levels 2187.28N and 10.65MPa (the upper), 3867.63N and 11.97MPa (the middle) and 5892.03N and 12.81MPa (the lower); in the radial compression of the stalks, the average values of the failure load and compressive strength were respectively for different levels 345.40N and 1.24MPa (the upper), 542.90N and 1.19MPa (the middle) as well as 662.97N and 1.09MPa (the lower). For the sliding cutting, the range of the failure load was between 241.22~1150.32 N with an average value of 662.30 N and the range of the strength was between 1.55~7.51MPa with an average value of 4.20MPa. For the cutting, the range of failure load was between 261.84~1235.64 N with an average value of 649.24N and the range of the strength was between 1.12~4.99MPa with an average value of 2.17MPa. The ANOVA results showed that the impacts of the moisture content and the stalk levels on the axial compressive strength were significant (P0.05). The sliding cutting angle and loading rates respectively had a significant and a highly significant impact on the sliding cutting strength (P<0.05), as well as the moisture content, cutting angle and loading rate were significant to the cutting strength (P<0.05).
Keywords: Cassava Stalks; Mechanical Properties; Compression; Shearing